2023
DOI: 10.1039/d3qo90021e
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Electrochemical tandem cyclization to access sulfonylated fused sultams via SO2 insertion with sodium metabisulfite

Abstract: Correction for ‘Electrochemical tandem cyclization to access sulfonylated fused sultams via SO2 insertion with sodium metabisulfite’ by Yun-Hai Sun et al., Org. Chem. Front., 2023, 10, 705–711, https://doi.org/10.1039/D2QO01821G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 2023, the same group discovered a novel electrochemical three-component coupling of Na 2 S 2 O 5 , N -cyanamide alkenes 47 and readily available sulfonyl hydrazides 48 for the assembly of various sulfonylated fused sultams 49 in a sustainable and modular fashion (Scheme 17 ). 23a The N–S and S–C bonds for the construction of fused sultams were established by applying cost-effective and easy-to-handle sodium metabisulfite as an SO 2 surrogate for the transformation in an undivided electrolysis cell without a supporting electrolyte. The protocol embraced a broad substrate scope, among which N -aryl cyanamide alkenes 47 with either electron-donating or electron-withdrawing groups at the para position of the benzene ring of the cyanamides were amenable to this reaction.…”
Section: Electron-induced Radical Cyclizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2023, the same group discovered a novel electrochemical three-component coupling of Na 2 S 2 O 5 , N -cyanamide alkenes 47 and readily available sulfonyl hydrazides 48 for the assembly of various sulfonylated fused sultams 49 in a sustainable and modular fashion (Scheme 17 ). 23a The N–S and S–C bonds for the construction of fused sultams were established by applying cost-effective and easy-to-handle sodium metabisulfite as an SO 2 surrogate for the transformation in an undivided electrolysis cell without a supporting electrolyte. The protocol embraced a broad substrate scope, among which N -aryl cyanamide alkenes 47 with either electron-donating or electron-withdrawing groups at the para position of the benzene ring of the cyanamides were amenable to this reaction.…”
Section: Electron-induced Radical Cyclizationmentioning
confidence: 99%
“…The proposed mechanism 23b indicated that the anodic oxidation of A led to the generation of a Ts radical. Subsequent addition of this Ts radical to the terminal alkyne of B gave intermediate C , which underwent intramolecular cyclization to afford iminyl radical D .…”
Section: Electron-induced Radical Cyclizationmentioning
confidence: 99%